El testimonio poético de María Marián en el poemario "Como cuando se riega jacintos tiernos" - Tauma Romero, Patricia Victoria (2022)
María Marián is the pseudonym of the huancaine poet Raquel Prialé Jaime (1927), who, at 85 years of age, dared to publish her first collection of poems As when tender hyacinths are watered (2012). In the last century, many women shied away from writing and publishing because they didn’t want to be vulnerable by exposing part of their privacy to biased criticism. A poet from the interior of the country had to face double discrimination: for being a woman and for being from the province, however, in this century, progress is being made in the process of a just claim. For this reason, Raquel Prialé’s collection of poems acquires a great significant value as a poetic testimony of an intense life.